1998
DOI: 10.1148/radiology.207.1.9530300
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolesions at T1-weighted gradient-echo imaging after administration of superparamagnetic iron oxide: comparison with portal perfusion abnormalities at CT during arterial portography.

Abstract: Impaired portal perfusion decreased the uptake of SPIO in histopathologically normal regions of liver parenchyma. Resultant differences in signal intensity were better visualized on GRE than on turbo SE images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…13 Impaired portal perfusion decreased the uptake of SPIO in histopathologically normal regions of the liver parenchyma. Scharf et al 18 suggested that tumor-associated portal perfusion defects are associated closely with impaired uptake of SPIO and that the uptake is not diminished in most non-tumorassociated perfusion defects. The difference in the effect of SPIO is more obvious on the T2*-weighted gradient-echo images than on T2-weighted turbo spinecho images.…”
Section: Discussionmentioning
confidence: 99%
“…13 Impaired portal perfusion decreased the uptake of SPIO in histopathologically normal regions of the liver parenchyma. Scharf et al 18 suggested that tumor-associated portal perfusion defects are associated closely with impaired uptake of SPIO and that the uptake is not diminished in most non-tumorassociated perfusion defects. The difference in the effect of SPIO is more obvious on the T2*-weighted gradient-echo images than on T2-weighted turbo spinecho images.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that impaired portal perfusion might decrease the uptake of SPIO in histopathologically normal liver parenchyma (31), resulting in reduced signal loss at SPIO-enhanced MRI. Mori et al (32) also reported that since Kupffer cells and hepatocytes are not injured in nontumorous APS without obstruction of the portal vein, the signal loss was more pronounced in tumorous APS in which the associated portal branches were obstructed, than in nontumorous APS.…”
Section: Imaging Findingsmentioning
confidence: 99%
“…Subsequently, researchers described the usefulness of ferumoxide-enhanced T1-weighted GE imaging (13)(14)(15)17), showing that this sequence acquired images of the entire liver during a single breath hold and possessed high signal-to-noise ratios yielded by its shorter echo time and higher flip angle. Among them, Nakayama et al (17) reported that the frequency of a perilesional hyperintense rim was significantly greater with metastasis than with hepatocellular carcinoma (79% versus 14%).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, some researchers (12)(13)(14)(15)(16)(17) have described the imaging findings or usefulness of T1-weighted MR imaging following administration of superparamagnetic iron oxide compound. Some studies (16,17) have described that the perilesional ring enhancement, observed on T1-weighted MR images following administration of superparamagnetic iron oxide compound, may help characterize focal hepatic lesions as malignant or not.…”
mentioning
confidence: 99%